Study of phase theory in Rhammatocerus schistocercoides (Orthoptera : Acrididae) in oriental plains of Colombia - EBRATT, EVERTH E.; ESPINEL, CARLOS; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2000)
An invasion of the llanera locust Rhammatocerus schistocercoides ocurred in 1994 in the Oriental Plains of Colombia, causing damages in agricultural and cattle production of the region. Previous studies of this species demonstrated that three biotypes: green, brown, and red are present on individuals of the same population. The phase polymorphism theory expresses that Acrididae may change of a solitarious to a gregarious phase or vice versa, expressing changes in morphometric characteristics in colorations and in behavior. These insects are considered are true locusts. Although R. schistocercoides have a gregarious behavior is not recognized as a locust, therefore the objective of the work was to verify the presence of phase polymorphism in this species. Green nymphs were placed in cages individually and groups and the changes of the coloration was observed in order to describe the morphological and coloration characteristics in females and males adults belonging to biotypes red, brown (gregarious) and green (solitarious). The length of the elytron, hind femur and pronotum, and width of the head were also measured. With this data were made the index elytron/femur (E/F) and femur/head (F/H), recommended to determine differences between polymorphic states. The obtained results permitted conclude that exists a group effect in nymphs of the species, due to the coloration change toward instar. Significatives differences were also found between E/F and F/H index on green and red biotypes, and in E/F on green and brown biotypes. Moreover, these insects did not present differences for the E/F index between red and brown biotypes, neither for the F/H index between green and brown biotypes. We could demonstrate that exists phase polymorphism in R. schistocercoides, between green (solitarious) and red (gregarious) biotypes, so this species can be considered as a true locust.